The Impact of Childhood Obesity on Mental Health: A Comprehensive Review - Spychalski, Jan; Musiał, Mikołaj; Spychalska, Maria; Dylik, Adrianna; Gryczyńska, Weronika; Grochowska, Wiktoria; Kaczmarek, Mikołaj; Krawczak, Łukasz; Gulaczyk, Hanna (Quality in Sport, 2024)
Introduction: Obesity and overweight are among the main health issues affecting the child population in developed countries today. Excess body weight is observed in 29.7% of boys and 14.3% of girls aged 11 to 16 years. Studies reveal that childhood overweight increases the odds of having mental disorders in adolescence compared to children with a normal body weight. Aim of the study: The aim of this study is to analyse the available literature in order to examine the impact of childhood obesity on mental disorders such as depression, anxiety, ADHD, eating disorders and schizophrenia, Materials and methods: Comprehensive review of the literature available on PubMed, Google Scholar, Scopus database by searching the keywords “obesity”, “overweight”, “ mental health”, “childhood”, “mood disorders” “psychiatric disorders”, “anxiety”, “depression”, “eating disorders”, “ADHD” Results and conclusion: Childhood obesity is a growing global problem with physical and health consequences. It is associated with various factors such as social stigma, neurological imbalances or malfunction and other environmental factors related to obesity. It contributes to the growth of depression, ADHD, anxiety, eating disorders, OCD and even schizophrenia. Preventing and treating obese or overweight children have to be done, by affecting both physical and mental health.